Decentralization of Education: Opportunities and Challenges for Central Government, Provincial Government and Regional Government in Management of Education - Oskar, Ruani; Putra, Fahmi Mandala; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
The issuance of Law Number 23 of 2014 concerning Regional Government provides broader autonomy to each region (Province) and Region (Regency/City) to regulate their own regions. In the realm of Education, this autonomy not only builds independence but also raises other problems that complicate regional government. With a qualitative approach using the Literature Study Analysis method with Primary Data in the form of Law Number 23 of 2014 and Law Number 20 of 2003 as the Main Data from several Journals, several Government problems can be found related to the distribution of authority such as Coordination Between Levels of Government, Human Resource Capacity, Funding and Budget, Management of Educators and Infrastructure and Facilities. The resolution of the problems that have been conveyed requires efforts to improve coordination between levels of government, strengthening the capacity of human resources in the regions, clarity in budget allocation, and equal distribution of educators and development of educational infrastructure. It is hoped that this article can provide an overview of micro problems in the regions and then sit together to solve these problems.